7-Ketocholesterol promotes T cell migration through Ca2+-NFATc1 pathway-mediated F-actin polymerization and proinflammatory cytokine production in oral lichen planus - Jiang, Qin; Tang, Yu-Xi; Zhou, Gang (Frontiers in Immunology, 2026)
BackgroundOral lichen planus (OLP) is a chronic T-cell-mediated inflammatory disorder of unknown etiology. Accumulating evidence has demonstrated elevated cholesterol levels in OLP, and its oxidation products --oxysterols have been implicated in T cell dysfunction. However, whether the oxysterol is involved in OLP pathogenesis remains to be fully elucidated.MethodsMetabolomics was performed to profile oxysterols in the plasma of OLP patients, followed by functional enrichment analysis. Single-cell RNA sequencing was utilized to characterize gene expression dysregulation in tissue-resident T cells isolated from OLP lesions. Flow cytometry, immunofluorescence, and qRT-PCR were collectively used to quantify Ca2+ concentration, cell apoptosis, protein expression, intracellular signaling, and gene transcription levels. Functional validation was conducted through a co-culture model and Transwell migration assays to assess the cytotoxic and migratory capacity of OLP T cells.ResultsThe oxysterol profiles were aberrant in OLP plasma, with marked accumulation of 7-ketocholesterol (7KC). Functional analysis identified significant enrichment of differential metabolites in androstenedione metabolism. 7KC upregulated the expression of cholesterol regulators (SREBP2/LXR) in OLP T cells. Pro-7-ketocholesterogenic gene sets were dysregulated in OLP tissues, with localized T cells exhibiting enriched Ca2+ -NFATc1 signaling and coordinated F-actin polymerization/ITGAL (LFA-1α) upregulation, positively correlating with migration signatures. Peripheral OLP T cells showed elevated Ca2+, nuclear NFATc1, F-actin polymerization, and LFA-1α, all of which, along with ITGAL/IL1B/CCL4/IL6 levels, were further potentiated by 7KC treatment. 7KC was confirmed to enhance migrations of primary OLP T cells and OLP plasma-pretreated Jurkat T cells toward LPS-treated keratinocytes, without affecting keratinocyte apoptosis. Furthermore, CM4620-mediated blockade of Ca2+ -NFATc1 pathway in OLP T cells inhibited 7KC-induced NFATc1 activation, reduced the expressions of F-actin and its modulators ACTB/DIAPH1, and IL1B/CCL4/IL6 gene expressions, with migration suppressions of both primary OLP T cells and OLP plasma-pretreated Jurkat T cells.Conclusions7KC could promote T cell migration through Ca2+ -NFATc1 pathway-mediated F-actin polymerization and expression of IL1B/CCL4/IL6 in OLP.